2022
DOI: 10.3390/brainsci12020195
|View full text |Cite
|
Sign up to set email alerts
|

Nonequivalent After-Effects of Alternating Current Stimulation on Motor Cortex Oscillation and Inhibition: Simulation and Experimental Study

Abstract: The effects of transcranial alternating current stimulation (tACS) frequency on brain oscillations and cortical excitability are still controversial. Therefore, this study investigated how different tACS frequencies differentially modulate cortical oscillation and inhibition. To do so, we first determined the optimal positioning of tACS electrodes through an electric field simulation constructed from magnetic resonance images. Seven electrode configurations were tested on the electric field of the precentral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
(145 reference statements)
0
13
0
Order By: Relevance
“…Previous studies suggested that PAS may induce the reinforcement of cortical excitability in GABA A - and GABA B -ergic cortical circuits [ 9 , 17 ]. Therefore, unconditioned MEPs, GABA A -mediated short-interval intra-cortical inhibition (SICI), and GABA B -mediated long-interval intra-cortical inhibition (LICI) were measured at of each FCR (i.e., agonist) or ECR (i.e., antagonist) muscle before and after PAS-25 ms and PAS-10 ms [ 2 , 53 , 54 , 55 ]. Unconditioned MEPs were evoked at the of each FCR or ECR muscle at 120% of the RMT value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that PAS may induce the reinforcement of cortical excitability in GABA A - and GABA B -ergic cortical circuits [ 9 , 17 ]. Therefore, unconditioned MEPs, GABA A -mediated short-interval intra-cortical inhibition (SICI), and GABA B -mediated long-interval intra-cortical inhibition (LICI) were measured at of each FCR (i.e., agonist) or ECR (i.e., antagonist) muscle before and after PAS-25 ms and PAS-10 ms [ 2 , 53 , 54 , 55 ]. Unconditioned MEPs were evoked at the of each FCR or ECR muscle at 120% of the RMT value.…”
Section: Methodsmentioning
confidence: 99%
“…For SICI, the stimulus intensity for the first conditioning pulse was set at 80% of the FCR muscle’s RMT, whereas the second test pulse was set at 120% of the FCR muscle’s RMT. An interstimulus interval of 2.5 ms was used to test SICI [ 53 , 54 , 55 ]. For LICI, the stimulus intensity was set at 120% of the RMT for both the conditioning and test stimuli, and 100 ms was used as the interstimulus interval [ 2 , 56 , 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…28.5% in net electric field strength was linked to an effect size of .78 and thus supports the increase in the tES efficacy based on individual current flow modeling, taking the effective intensity into account. Similarly, Suzuki et al (2022) selected the electrode montage for tACS of the motor cortex based on individual modeling and used a group‐level analysis of the electric field strength in the precentral knob. They identified the montage Cz–CP1 to produce the most intense (factor 2) and least variable (factor 4) electric field intensity in the target area.…”
Section: Induced Field and Stimulation Montage Based On Individual Mo...mentioning
confidence: 99%
“…Moreover, Suzuki et al [ 4 ] investigated motor cortex stimulation using different transcranial alternating current (tACS) protocols (alpha-tACS at 10 Hz vs. beta-tACS at 20 Hz vs. sham) in a randomized sham-controlled crossover study involving 16 healthy individuals. After testing several setups, they adopted the Cz-CP1 setup (according to the electroencephalographic (EEG) system for electrode positioning), which appeared to be optimal for targeting the hand motor area.…”
Section: Neurophysiology and Neurostimulationmentioning
confidence: 99%